STRATEGI KEPEMIMPINAN TECHNOPRENEUR KEPALA SEKOLAH DALAM MENGINTEGRASIKAN TEKNOLOGI DIGITAL GUNA MENUMBUHKAN KREATIVITAS PEMBELAJARAN DI SMPN 1 PULOKULON - Dewi Lestari Kristiyaningsih; Slamet Slamet (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The massive digital transformation in the era of the Fourth Industrial Revolution requires school principals to reposition their roles from conventional managers to visionary and innovative leaders. This study aims to analyze the dynamics of technopreneurial leadership among school principals in developing a creative digital learning ecosystem at SMPN 1 Pulokulon. The research employed a qualitative approach with a case study design, in which the researcher served as the primary instrument through in-depth interviews, participant observation, and documentation studies. Data were analyzed inductively using the Miles, Huberman, and Saldaña model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that technopreneurial leadership is manifested through strategic planning based on SWOT analysis, the reconfiguration of physical assets into a